Factors Impacting Sumatran Private Medical Students Inclination to Work In Rural Areas - Fadilah, Mariatul (Advances in Social Sciences Research Journal, 2021)
At present the progress of Indonesia’s health currently has significant problems with the unequal distribution of doctors in rural areas; doctors are only concentrated in urban areas. The environment and policies at private universities have a big influence on the educational process, which causes the low interest of private medical students to work in rural areas. Getting the right results on the pattern of interest in private medical students to work in rural areas will ultimately help policymakers to resolve differences in the distribution of doctors in Indonesia. This quantitative analytical study was conducted at 12 private medical faculties on the island of Sumatra, Indonesia. The total sample obtained was 446 active private medical students in 2016 from a total population of 5,106 students. Data were collected by questionnaire and analyzed using software namely SPSS. From the results of the binary logistic regression analysis, there are four dominant factors of private students that affect the interest in working in rural areas. Then a multivariate logistic regression analysis using the enter method was conducted that the tendency of medical students to work in rural areas was 58% for private universities. By using patterns and student acceptance variables, it is expected to increase the interest of private medical students working in rural areas, and ultimately be able to distribute doctors equally in Indonesia.